Penyebab Mortalitas Lansia Selama Masa Perawatan Rumah Sakit COVID-19: A Systematic Review - Agnes Dewi Astuti; Bernadetta Germia Aridamayanti (FORIKES, 2021)
Background: The first case of COVID-19 was first reported in China in December 2019 and spread rapidly to various countries. On July 13, 2020, COVID-19 was officially declared a world pandemic by the WHO. COVID19 affects more than 210 countries in the world and kills millions of people with 21% of deaths occurring in the elderly. Objective: To describe the risk factors and causes of elderly mortality during the period of treatment or quarantine in the hospital by COVID-19. Methods: The database used as a reference, among others, is Scopus, PubMed and Science Direct, which is limited to publications in the last 2 years from 2020 to 2021, full text articles selected in English. Meanwhile, the keywords used in the article search are